Rapid Progressive Glomerulonephritis In Drug-Induced Bullous Pemphigoid - Dewiastuti, Marlina; Bonar, Maruhum (Syntax Corporation, 2026)
Rapidly progressive glomerulonephritis (RPGN) is a nephrologic emergency characterized by a rapid decline in renal function over days to weeks and is often associated with active urinary abnormalities. Drug-induced bullous pemphigoid (DIBP) is an autoimmune subepidermal blistering disease triggered by medication exposure and typically shows complement involvement. We report a case of a 62-year-old man with diabetes mellitus who developed pruritic urticarial plaques and tense bullae with erosions and hemorrhagic crusts on the trunk and extremities, predominantly on the dorsal hands and forearms, two days after starting acarbose. During hospitalization, renal function deteriorated rapidly within days, accompanied by significant albuminuria. The Naranjo Adverse Drug Reaction Probability Scale score was 5, indicating a probable drug-related reaction. Acarbose was discontinued and the patient received high-dose systemic corticosteroids (500 mg/day for three days). After seven days of therapy, renal parameters improved. Although renal biopsy and comprehensive serologic work-up were not performed to confirm the exact subtype of crescentic glomerulonephritis, the temporal association, probable causality assessment, and clinical response support an immune-mediated process with concurrent skin and kidney involvement. This case highlights the importance of early renal evaluation and multidisciplinary management in patients with suspected DIBP, as prompt drug withdrawal and immunosuppressive therapy may prevent irreversible kidney damage.